Determination And Identification the Awareness of Primary Eye Care in Community: Awareness of Primary Eye Care in Health care worker of Community - Jan, Nawar; Anjum, Misra; Ahmad, Muhammad; Anwar Faridi, Tallat; Iqbal, Samia; Mujahid, Muhammad; Hussain, Abid (Pakistan BioMedical Journal, 2022)
Vision is the essential part of our life. A good eye health is necessary to perform a lot of works such as cooking, sewing, studding, driving. it affects our social, economic life. Vision also affects the quality of life and a person’s physical and mental state. Objective: The study’s main goal was to find out how much people in the community knew about primary eye care. Methods: A cross-sectional survey with questionnaires was done. The research site, target population, sample size (194 people), sampling method, research methodology, and work plan were all chosen. Results: The level of knowledge and awareness in the community was about average. Most people don’t know much about primary eye care because there aren’t many places to get information, and they can’t access services. The study had 194 people sign up, of which 48.9% were men and 52.2% were women. 58.9% of the participants of study, were well aware and knew about basic eye care. Associated factors with awareness of Health care worker of community about Primary Eye Care showed significant association. Conclusion: Most people in the community know about primary eye care, and the results of this study seem to back up what they know. However, teaching people about primary eye care and eye care services is time. I would suggest through this study, to take extra measures to improve general awareness about eye care in community through social media and print media or papers so that people can avoid common eye diseases.